PENGARUH KECERDASAN EMOSIONAL DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT LAJU PERDANA INDAH DI OKU TIMUR - Dita Marisa Putri; Syaiful Sahri (JURNAL KOMPETITIF, 2021)
Effect of Emotional Intelligence and Job Stress on Employee Performance at PT Laju Perdana Indah in East Oku. The aims of this study are (1) to determine the effect of emotional intelligence and work stress together on employee performance at PT Laju Perdana Indah in East Oku. (2) To determine the effect of emotional intelligence on employee performance at PT Laju Perdana Indah in East Oku. (3) To determine work stress on employee performance at PT Laju Perdana Indah in East Oku. The results of the study show that simultaneously or together there is an influence of Emotional Intelligence (X1) and work stress (X2) on Employee Work Performance (Y) this can be seen from the results of the F test (ANOVA). 0.05. From the results of the simple Correlation Coefficient Test analysis, the correlation value between the Emotional Intelligence variable and the employee work performance variable is 0.811, this number indicates that there is a strong correlation between the Emotional Intelligence variable and the employee work performance variable. Likewise, the correlation value between the work stress variable and the employee work performance variable is 0.811. This number also shows that there is a strong correlation between the work stress variable and the employee work performance variable.